A Safe and Inclusive Learning Environment: A Comprehensive Review from the Perspectives of General and Islamic Education - Muhamad Fadillah (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
A safe and inclusive learning environment is an essential prerequisite for creating an effective and meaningful educational process. This article aims to analyze the concepts, components, strategies, challenges, and benefits of safe and inclusive learning environments within the context of general and Islamic education. The study employs a literature review method using a descriptive qualitative approach. The findings reveal that a safe and inclusive learning environment encompasses not only physical aspects but also social, cultural, and psychological dimensions. Teacher competence plays a central role in fostering such an environment, including pedagogical, professional, personal, social, and managerial competencies. Major challenges identified include bullying, sexual violence, and seniority culture. Strategies that can be implemented include strengthening school policies, providing teacher training, involving parents and communities, and applying positive discipline practices. This article is expected to serve as a reference for educators, educational institution managers, and policymakers in creating a conducive learning environment for all students.